2009
DOI: 10.1186/1758-5996-1-29
|View full text |Cite
|
Sign up to set email alerts
|

Association of the components of the metabolic syndrome with non- alcoholic fatty liver disease among normal-weight, overweight and obese children and adolescents

Abstract: ObjectivesThis study aimed to determine the prevalence of the metabolic syndrome, abnormalities of liver enzymes and sonographic fatty liver, as well as the inter-related associations in normal weight, overweight and obese children and adolescents.MethodsThis cross-sectional study was conducted among a sample of 1107 students (56.1% girls), aged 6-18 years in Isfahan, Iran. In addition to physical examination, fasting blood glucose, serum lipid profile and liver enzymes were determined. Liver sonography was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 33 publications
7
49
2
1
Order By: Relevance
“…Habitually, in children, NAFLD is asymptomatic, and increased serum of aminotransferase is a predictor of NAFLD [22,62]; however, normal serum levels of these liver enzymes do not exclude the existence of the disease [19,61]. It is reported that hyperinsulinemia plays a significant role in the genesis of fatty liver, and hepatic insulin resistance may be the underlying pathogenetic factor linking obesity and NAFDL [19,63,64,65,66]. Insulin resistance results in increased elaboration of free fatty acids that are absorbed by the liver, with consequent steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Habitually, in children, NAFLD is asymptomatic, and increased serum of aminotransferase is a predictor of NAFLD [22,62]; however, normal serum levels of these liver enzymes do not exclude the existence of the disease [19,61]. It is reported that hyperinsulinemia plays a significant role in the genesis of fatty liver, and hepatic insulin resistance may be the underlying pathogenetic factor linking obesity and NAFDL [19,63,64,65,66]. Insulin resistance results in increased elaboration of free fatty acids that are absorbed by the liver, with consequent steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…A major contributor to fatty liver is enhanced de novo synthesis of fatty acids (lipogenesis) which leads to hepatic steatosis. Kelishadi et al (9) suggested that, in future interventional studies, in addition to liver en zymes, high-sensitive CRP, gGT, uric acid, vitamin D, adi ponectin, ghrelin level, insulin level, insulin resistance and the oral glucose tolerance test could be the integral part of the evaluation of patients with NAFLD to further clarify the relationships among different biologic factors and the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD includes different types of liver pathologies and outcomes, from simple steatosis to nonalcoholic steatohepatitis (NASH) (9). NAFLD usually develops in children who are obese (10).…”
Section: Introductionmentioning
confidence: 99%
“…Kelishadi et al [23] have in fact reported that in 1,107 Iranian subjects (aged 6-18 years) central obesity may be used as a predictor of NAFLD assessed by ultrasound and surrogate markers, such as alanine aminotransferase (ALT). Accordingly, Wei et al [24] have demonstrated that approximately 16% of a cohort of obese British children display an increase of serum ALT levels, elevated BMI and altered glucose homeostasis.…”
Section: Role Of Central Obesity-dependent Inflammation and Insulin Rmentioning
confidence: 99%